Penerimaan Dakwah Keagamaan Mubaligh Tradisional dalam Masyarakat Korban Gempa Bumi - Nelmaya Nelmaya; Ali Rahman; Silfia Hanani (Turast: Jurnal Penelitian dan Pengabdian, 2019)
This study aims to describe the influence of traditional religious elites (Mubaligh) in Nagari Tandikek, Patamuan sub-district, Padang Pariaman district, which experienced an earthquake outside of September 30, 2009. Qualitative research type is used to collect the data. Observation and interview techniques are used to collect the data. The result shows that the traditional religious leaders are very influential in the Tandikek community. They have transformative and communicative approaches which are very easily understood by the communities. In addition, religious elites are also able to become a reference figure in acting and behaving. It is concluded that religious elites has important role in stimulating communities.